(untitled) - Wlter Laqueur (New York, 1992)
Less than fifty years ago, Europe was a continent in ruins, shattered by the Second War and sundered into two blocs. Today its nations are merging into a single common European market comprising more than three hundred million people - an economic superpower rivaling Japan and the United States. The book provides an incisive chronicle of the continent's political, economic, social, and cultural evolution from the origins of the Cold War to the fall of the Berlin Wall - with a particular emphasis on the pivotal events of the last twenty years. Including a detailed, country-by-country analysis of Europe's most recent history - the events leading up to the reunification of Germany, the Thatcherite Revolution in Britain, France since the death of De gaule, Spain after Franco, the Soviet Union under Brezhnev and Gorbachev, the "de-Sovietization" of Eastern Europe
Keywords: europe - history - 1945-